58 Multidisciplinary surgical approach to increase complete cytoreduction rates for advanced ovarian cancer in a tertiary gynaecological oncology centre. (13th November 2020) - Mulligan, K; Glennon, K; Donohoe, F; O'Brien, Y; Mc Donnell, R; Bartels, H; Vermeulen, C; Walsh, T; Shields, C; Mc Cormack, O; Conneely, J; Boyd, W; et al.
Abstract : Objective: The aim of this paper is to report on changes in complete cytoreduction rates and morbidity following the implementation of a multi-disciplinary surgical team including gynaecological oncologists, colorectal and upper GI surgeons in a tertiary gynaecological oncology unit. In 2017 we implemented a multi-disciplinary surgical team including gynaecological oncologists, colorectal, hepatobiliary and upper GI surgeons to increase gross macroscopic resection rates. Methods: Two cohorts were used. Cohort A was a retrospectively collated cohort from 2006–2015. Cohort B was a prospectively collated cohort of patients initiated in 2017. A multidisciplinary approach to preoperative medical optimisation, intra operative management and postoperative care was implemented in 2017. Patients in cohort B with upper abdominal disease were offered primary cytoreduction ± HIPEC. Prior to 2017 patients with upper abdominal disease received neoadjuvant chemotherapy. Results: This study include 146 patients in cohort A (2006–2015) and 93 patients in cohort B (2017–2019) with stage III/IV ovarian cancer. The overall complete macroscopic resection rate (CC-0) increased from 58.9% in cohort A to 67.7% in cohort B. The rate of primary CRS increased from 38% (55/146) in cohort A to 42% (39/93) in cohort B. The CC-0 rate in those who had primary CRS increased from 49% in Cohort A to 77% in Cohort B. Major morbidity remained stable throughout both study periods. Conclusions: Our data demonstrates that the implementation of multidisciplinary team intraoperative approach and a meticulous approach to preoperative optimisation has resulted in an significant improvement in complete resection rates particularly in women offered primary CRS.